ANALISIS STRUKTUR KARAKTERISASI XRD DAN SEM PADA REDUCED GRAPHENE OXIDE (rGO) LIMBAH BAN - Sandi Tri Febriani; Ety Jumiati; Miftahul Husnah (Universitas Riau, 2023)
Research has been carried out using waste tires as the basic material for reduced graphene oxide (rGO). This research has been successfully synthesized using waste tire smoke with combustion and microwave assisted methods as a faster, easier, and safer synthesis process. The characterizations used in this research are X-ray diffraction (XRD) and scanning electron microscope (SEM). The powder is obtained through the process of capturing smoke from burning waste tires manually at a temperaturre of 300°C for 3 hours. Then it was reduced using microwave heating with variations in heating time of 20, 25, and 30 minutes. The results of the XRD characterization data showed a diffraction peak (002) peak at 2θ = 25° and a diffraction peak (101) peak 2θ = 43.9° which identified rGO and the results of the SEM characterization test obtained that the surface morfology formed a thin sheet.